ADOPTION OF BIOTECHNOLOGIES FOR MORE EFFICIENT REVEGETATION BY PIG BEANS AND CROTALARIA IN IRON ORE TAILINGS (Colloquium Agrariae. ISSN: 1809-8215, 2020)
Many times prevented from natural regeneration, areas degraded by ore tailings must follow measures aimed at their environmental recovery, such as revegetation by correct species, whose result can still be enhanced by the use of bio-stimulants, contributing to improvements in soil fertility through efficient green manure, favoring increased production of plant biomass and then the cycling of nutrients in the soil-plant system. The objective was to evaluate the dry matter production, accumulation and nutrient export rates by pig bean plants (Canavalia ensiformis) and Crotalaria juncea cv. IAC-KR-1 as a function of the application of humic substances and diazotrophic bacteria. The experiment was conducted in a green house using iron ore tailings as substrate. An experimental design of random blocks (4x3x2) was used with four repetitions, four doses of humic substances, applied at 3 different times, with or without inoculation of diazotrophic bacteria. The supply of humic substances and mainly the inoculation in both species increased the dry matter production, reaching 70% of the average increase in pig beans. Inoculation in pig bean plants increased the absorption and transfer factor of Fe and P, and reduced the transfer factor of K, Ca and Mg, and in crotalaria plants increased the absorption of Mg, P and Mn, and reduced the absorption of Fe. The high content of Fe in mining tailings culminated in high absorption and mobilization of this element in the roots of the plants as an alternative to minimize toxic effects caused by its excess.